Analysis of pigment composition of brown seaweeds collected from Panjang Island, Central Java, Indonesia - Heriyanto; Juliadiningtyas, Ayu Dita; Shioi, Yuzo; Limantara, Leenawaty; Brotosudarmo; Tatas Hardo Panintingjati (2017)
Composition of pigments from four species of brown seaweeds (Phaeophyceae) collected from Panjang Island, Central Java, Indonesia, was investigated with spectroscopic method and reverse-phase high-performance liquid chromatography (RP-HPLC). Identification of pigments was based on their spectral and chromatographic properties and also confirmed by electrospray ionization-mass spectrometry (ESI-MS/MS) analysis. The experimental results showed that concentrations of chlorophyll a (Chl a) and total carotenoids (Cars) from brown seaweeds, estimated by spectroscopic method, varied depending on species from 1.73 mg ? g?1 to 8.84 mg ? g?1 and from 0.55 mg ? g?1 to 4.06 mg ? g?1 dry weight (dw), respectively. In addition, the order of concentrations of Chl a and total Cars in four species of seaweed was as follows: Dictyota dentata > Padina australis > Sargassum crassifolium > Turbinaria conoides. This order was in agreement with the concentrations of dominant pigments calculated by HPLC method, i.e., fucoxanthin (Fuco) (0.43 mg ? g?1 to 4.11 mg ? g?1 dw), Chl a (1.70 mg ? g?1 to 7.89 mg ? g?1 dw), β-carotene (0.16 mg ? g?1 to 0.78 mg ? g?1 dw). These results suggest that D. dentata is likely potential source material to explore the industrial utilization, especially functional food and biomedical ingredients, of Fuco and Chl a. (Author's abstract)
Includes bibliographical references (pages 329-330)
Keywords: Fisheries; Brown seaweed; Chlorophyll a; Esi-ms/ms.; Fucoxanthin; Panjang island - Analysis of pigment composition of brown seaweeds; Pigment composition